DINAMIKA POPULASI SAPI POTONG DI KECAMATAN PAMONA UTARA KABUPATEN POSO - Tanari, Mobius; Duma, Yulius; Rusiyantono, Yohan; Mangun, Mardiah (AgriSains, 2011)
The objective of this research was to identify the dynamic population of beef cattle at North Pamona of Poso regency. This research was an analytical descriptive study conducted using survey method on 572 respondents taken using a purposive sampling method from all villages at         North Pamona. The result showed that the composition of beef cattle were 533 (34.88%) bull and 995 (65.12%) cows. The total number of bull calves, bullock and bull were 93, 100 and 340, respectively, while the heifer calves, heifers and cows were 135, 130 and 738 respectively.          The birth rate was 30.89% or 14.83% of the total population whereas the motility rate was 2.7% so that the natural increase was 12.13%.  Key words: Beef cattle, population and reproductivity.